ANALISIS DETERMINAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DESA DI WILAYAH KECAMATAN LAWEYAN SURAKARTA - Deni Fitriani; Endang Masitoh; Purnama Siddi (ITB AAS INDONESIA, 2022)
This study aims to examine and analyze the effect of Government Accounting Standards (SAP), Regional Financial Accounting Systems (SAKD), Government Internal Control Systems (SPIP), and HR competencies on the quality of financial reports. This study uses a type of research with a quantitative approach, where the instrument uses a questionnaire. The research sample was 58 respondents. The data analysis method used in this research is multiple linear regression for testing the research hypothesis. The results of the study prove that Government Accounting Standards (SAP) and HR competencies have no influence on the quality of financial reports. Meanwhile, the Regional Financial Accounting System (SAKD) and the Government's Internal Control System (SPIP) have an influence on the quality of financial reports. The amount of variability that can be explained by the independent variable on the quality of financial statements is 37.5%, meanwhile, the remaining 62.5% is influenced by other variables not included in this research model. Keywords : Government Accounting Standards (SAP), Regional Financial Accounting System (SAKD), Government Internal Control System (SPIP), HR competence and quality of financial reports.